2020
DOI: 10.18502/ijph.v49i8.3894
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cytokine Profile and Hypertension among the Mercury-Exposed Residents of Temirtau Region in Central Kazakhstan

Abstract: Background: Mercury is a common environmental contaminant and it is also harmful to human health. Among reported toxicities, its harmful effect on hypertension is poorly documented. In Kazakhstan, Temirtau city has been reported to have a high level of mercury contamination from an acetaldehyde production factory. Therefore, we aimed to investigate the association between serum profile of cytokines and the development of hypertension among the exposed citizens. Methods: We selected 81 individuals for stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Concerning the high levels of IL-8, it has been reported that mercury induces the expression of IL-8 in macrophage and human glioblastoma astrocytoma (U-87 MG) cell cultures, indicating that the IL-8 production may be a mechanism of action of neurotoxicity (Yamamoto et al, 2017). Similarly, this study corroborates the findings reported in residents of Kazakhstan exposed to mercury, which reported increased levels of the cytokine IL-2 (Shinetova et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the high levels of IL-8, it has been reported that mercury induces the expression of IL-8 in macrophage and human glioblastoma astrocytoma (U-87 MG) cell cultures, indicating that the IL-8 production may be a mechanism of action of neurotoxicity (Yamamoto et al, 2017). Similarly, this study corroborates the findings reported in residents of Kazakhstan exposed to mercury, which reported increased levels of the cytokine IL-2 (Shinetova et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The molecules regulate cell apoptosis by forming dimers of different quality and quantity. Studies have shown that IL-2 can induce the expression of BCL-2 (Shinetova et al, 2020), which may be mediated by NF-AT (Gómez et al, 1998). IL-2 can stimulate human peripheral blood lymphocytes to cause the accumulation of BCL-2α and β mRNA (Artyukhov and Tyunina, 2017;Pae et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Heaven et al [8] reported a range of Hg concentrations of 0.46-5.36 µg/L in the river Nura. Shinetova et al [50] measured 4.5 ± 9.8 µg/L (mean ± standard deviation) of Hg in highly contaminated parts and 0.03 ± 0.08 µg/L in low contaminated parts of the river Nura.…”
Section: Distribution Of Toxic Metals In the Water Of Rivers Lakes An...mentioning
confidence: 98%
“…The Karbide chemical plant is located on the river Nura in northeast-central Kazakhstan and the uncontrolled release of wastewater from the plant has resulted in serious contamination of the river [8]. This area, particularly Temirtau City, is known for high contamination with mercury and the citizens of the area were reported to have a higher risk of hypertension and higher blood concentrations of inflammatory markers [50]. Heaven et al [8] reported a range of Hg concentrations of 0.46-5.36 µg/L in the river Nura.…”
Section: Distribution Of Toxic Metals In the Water Of Rivers Lakes An...mentioning
confidence: 99%